Terbit Fajar dan Waktu Subuh (Kajian Nash Syar’i dan Astronomi) - Qomarus Zaman (MAHAKIM Journal of Islamic Family Law, 2018)
Fajr in syar’i concept is divided into two; Fajr Kazib and Fajar Shadiq. The Fajr Kazib is time to having breakfast before doing fasting and have no salah Subuh. The second is fajr Shadiq. It is time to have no having meal (because it is fasting time) and time to do salah Subuh. Fajr Kazib arises at the early morning whose the light is not bright, but it is longer to the top of East to West vertically. Then the sky comes dark like wolf tail. While Fajr Shadiq arises at the early morning whose light is bright spreading in East horizontally. It arises just before sunrise. Time between Fajr Shadiq and the sunrise is the time for salah Subuh. In Astronomy, the word Fajr means Morning Twilight. Twilight in Astronomy is divided into three; astronomical twilight, nautical twilight and civil twilight. First, astronomical twilight is as the end of night. That is when starlight is not bright because of sunrise. The sun position is level 18 below the horizon. At that time, there ios still dark because of the sun going to rise ( an hour and 12 minutes later the sun rises). The second is nautical twilight. It looks so bright is East horizon for the sailors who are going to land. The sun position is level 12 below the horizon (48 minutes later the sun rises). The third is civil twilight. It is Fajr whose the light is so bright in which the position is level 6 below the horizon. At that time, the sunlight is so really bright, and many people do their morning activities. And then 24 minutes later the sun rises.